2012
DOI: 10.1097/pas.0b013e31822d5ff8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detection of Spitzoid Melanomas Using Fluorescence In Situ Hybridization With 9p21 as an Adjunctive Probe

Abstract: The use of molecular diagnostic methods such as fluorescence in situ hybridization (FISH) for challenging melanocytic neoplasms is becoming more widespread. In light of the diagnostic difficulty they pose, spitzoid melanocytic neoplasms constitute an area of greatest potential utilization. In this study we wished to evaluate the sensitivity of the currently used melanoma FISH probe assay in a group of unambiguous spitzoid melanomas. On the basis of comparative genomic hybridization data, copy number losses at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 26 publications
6
72
1
Order By: Relevance
“…The sensitivity and specificity of the FISH method varies dramatically among existing reports with the lesion subtype, the probe set used, the number of observers, and the cutoff thresholds used. Various authors have reported a FISH sensitivity ranging from 43% to 94% and a specificity ranging from 60% to 98% 24, 25, 26, 27, 28. The original 4‐probe FISH assay targeting 6p25 (RREB1), 6q23 (MYB), Cep6 (centromere 6), and 11q13 (CCND1) was reported to discriminate between histologically unequivocal melanomas and benign nevi with a sensitivity of 86.7% and a specificity of 95.4% 24.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity and specificity of the FISH method varies dramatically among existing reports with the lesion subtype, the probe set used, the number of observers, and the cutoff thresholds used. Various authors have reported a FISH sensitivity ranging from 43% to 94% and a specificity ranging from 60% to 98% 24, 25, 26, 27, 28. The original 4‐probe FISH assay targeting 6p25 (RREB1), 6q23 (MYB), Cep6 (centromere 6), and 11q13 (CCND1) was reported to discriminate between histologically unequivocal melanomas and benign nevi with a sensitivity of 86.7% and a specificity of 95.4% 24.…”
Section: Discussionmentioning
confidence: 99%
“…The original 4‐probe FISH assay targeting 6p25 (RREB1), 6q23 (MYB), Cep6 (centromere 6), and 11q13 (CCND1) was reported to discriminate between histologically unequivocal melanomas and benign nevi with a sensitivity of 86.7% and a specificity of 95.4% 24. However, the sensitivity was subsequently found to be only 70% for melanomas with a Spitzoid morphology 25, 26, 29, 30, 31, 32…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that heterozygous losses of 9p21 were enumerated in both melanomas and nevi in the early stage of probe selection data, and as a result, the 9p21 probe failed to demonstrate a statistically significant difference between melanoma and nevi. 34 Current 5-probe FISH assay for diagnosis of melanoma. In 2012, after testing three training sets using 322 tumors, including 152 melanomas and 170 nevi, the initial FISH panel has been redefined to the currently used 5-probe set of 6p25, 9p21, CEN9, and 11q13, and myelocytomatosis oncogene (MYC, 8q24) (Figure 4b).…”
Section: Melanoma Fishmentioning
confidence: 99%
“…In 2012, after testing three training sets using 322 tumors, including 152 melanomas and 170 nevi, the initial FISH panel has been redefined to the currently used 5-probe set of 6p25, 9p21, CEN9, and 11q13, and myelocytomatosis oncogene (MYC, 8q24) (Figure 4b). 34 This probe set was validated on 51 melanomas and 51 nevi, and displayed improved discriminatory power with a sensitivity of 94% and specificity of 98% and significantly improved sensitivity of spitzoid melanoma detection to 94% (Table 3A and Figure 4b). 32 Table 3A summarizes the chronological improvement in sensitivity and specificity of the 4-and 5-probe FISH assay for the diagnosis of melanomas and demonstrates relatively consistent results between American and European groups even when different cutoff criteria were applied.…”
Section: Melanoma Fishmentioning
confidence: 99%
See 1 more Smart Citation